Training the Speaking Voice. - Anderson, Virgil A. (Virgil Antris), 1899-1994 (Oxford University Press, 1977)
Combines speech theory with practical exercises for developing proper vocal tone, resonance, expression, and breathing, articulation, and pronunciation skills.